Comparative Evaluation of Adaptation of Esthetic Prefabricated Fiberglass and CAD/CAM Crowns for Primary Teeth: Microcomputed Tomography Analysis. (26th September 2021) - Oguz, Ece Irem; Bezgin, Tuğba; Orhan, Ayse Isıl; Orhan, Kaan
Abstract : Adaptation is an important factor for the clinical success of restorations. However, no studies are available evaluating the adaptation of primary crowns. The aim of this study was to compare the adaptation of crowns fabricated by CAD/CAM technology versus prefabricated fiberglass primary crowns. Typodont maxillary central, canine, and mandibular molar teeth were prepared to serve as master dies after the size of Figaro crowns was determined (n = 10 ). Master dies were scanned with an intraoral scanner, and 10 identical CAD/CAM crowns were fabricated from resin-ceramic blocks. Figaro and CAD/CAM crowns were placed on the corresponding master dies and scanned via micro-CT. Three-dimensional volumetric gap measurements were performed to evaluate the overall adaptation. A total of 255 location-based linear measurements were allocated into 4 categories: marginal, cervical-axial, middle-axial, and occlusal. Statistical analyses were performed with factorial ANOVA, repeated measure ANOVA, and LSD tests (α = 0.05 ). CAD/CAM crowns showed significantly lower overall and location-based gap measurements than Figaro crowns regardless of tooth number (p < 0.05 ). For all groups, mean marginal discrepancies were lower than occlusal measurements (p < 0.05 ). Both crown types showed higher marginal gaps for molar teeth than for canine and central incisors with no significant difference between them (p > 0.05 ). CAD/CAM-fabricated crowns showed better marginal and internal adaptation than prefabricated Figaro crowns.